Coal Mine Workers Safety Helmet in Li-Fi Data Stored in Cloud - Vishnukumar, A.; A.Nirmal Kumar, Dr.; Velmurugan, J.; Pavithra, P.; Poornima, K.; Sabareessh, S. (International Journal of Engineering and Technology, 2018)
Â Coal miners are more likely affected by the various threatsÂ Â likeÂ Â gas explosion ,sudden healthÂ changesÂ andÂ issues,Â severeÂ changes of the temperature and the moisture level .In thisÂ paperÂ weÂ presentedÂ theÂ designÂ ofÂ Â the smart safety helmet for the coal miner using LI-FI, this helmet will be equipped with the networkÂ ofÂ sensorsÂ suchÂ asÂ theÂ heartbeat sensor ,humidity sensor,Â gas sensor and the temperatureÂ sensorÂ andÂ theÂ dataÂ from these sensors will be transmittedÂ using light fidelityÂ technologyÂ ,theÂ alertÂ messagesÂ are given to the mobile phones and also through theÂ mail to the authorized person using IOT. Many accidents which occur in the mining industriesÂ Â areÂ Â dueÂ Â toÂ Â theÂ Â Â Â Â slowÂ Â data transmissionÂ Â Â Â orÂ dueÂ toÂ theÂ lossÂ ofÂ data whichÂ hasÂ toÂ beÂ transmitted, Â theseÂ issues canÂ beÂ solvedÂ byÂ Â usingÂ Â theÂ Â light fidelity technologyÂ asÂ itÂ isÂ known for the fast data transmission .Â Â